Non-inferiority study to compare the efficacy of relugolix with dienogest for endometriosis-associated pain and usefulness of administering relugolix prior to dienogest (READY study): study protocol for a multicenter randomized controlled study - Fuminori Taniguchi; Motoko Fukui; Yutaka Osuga; Tasuku Harada; Jo Kitawaki (Trials)
Abstract Background Endometriosis presents as endometrial tissue growths outside the uterine cavity with its major symptoms including dysmenorrhea and infertility. Progestin preparations, such as dienogest, are the first-line therapy for endometriosis symptoms, but may cause abnormal uterine bleeding. A gonadotropin-releasing hormone (GnRH) agonist may also be used to ease symptoms, but may induce flare-ups. Relugolix is a non-peptide GnRH antagonist that does not induce flare-ups. This study aims to compare the efficacy of relugolix with that of dienogest for reducing endometriosis-associated pain, and to evaluate if relugolix, administered prior to dienogest, decreases abnormal uterine bleeding. Methods A multicenter, open-label, active-controlled, non-inferiority randomized study will be conducted at 11 sites in Japan. A total of 100 premenopausal patients aged ≥ 18 years with endometriosis, a maximum visual analog scale (VAS) score > 30 for endometriosis-associated pain, and dysmenorrhea or pelvic pain of at least moderate severity on the Biberoglu & Behrman (B&B) scale will be randomized in a 1:1 ratio to either a relugolix group or dienogest group. Patients in the relugolix group will receive 40 mg oral relugolix once daily for 16 weeks, followed by 1 mg oral dienogest twice daily for 24 weeks. Patients in the dienogest group will receive oral dienogest 1 mg twice daily for 24 weeks. The primary outcome will be change in maximum VAS score for endometriosis-associated pain from baseline to 13–16 weeks after start of treatment. The secondary outcomes will include VAS score for dyspareunia, B&B score for dysmenorrhea, severity of induration in the pouch of Douglas, restricted uterine mobility, pelvic tenderness, quality of life, analgesic use, and ovarian endometrioma diameter. The safety outcomes will include treatment-emergent adverse events, bone density, bone markers, menstrual status, genital bleeding, and endometrial thickness. Discussion This study will determine the efficacy of relugolix for improving endometriosis-associated pain and dienogest-induced abnormal uterine bleeding. The results will support treatment decisions regarding endometriosis-associated pain, and the introduction of new treatments to reduce dienogest-induced abnormal uterine bleeding. Trial registration Japan Registry of Clinical Trials ID jRCTs061230064. Registered on 29 September 2023.